PENGEMBANGAN FORMULA KRIM MINYAK SEREH (Cymbopogon citratus) SEBAGAI ANTI NYAMUK TOPIKAL - Lidya Ameliana; Evi Umayah Ulfa (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
Volatile oils extracted by steam distillation from Cymbopogon citratus were formulated in creams. Theessential oils were then employed as active ingredients in the preparation of insect repellents used in our field trials.These creams containing 0%; 0,5%; 1%; 5%; 10% and 15% (w/w) of volatile oil from Cymbopogon citratus. Thesecreams were evaluated in physical qualities like appearance, pH, spreadibility, and viscosity. And also wereevaluated for their repellency effect against adult female mosquitoes of Aedes aegypti. Results from the field trialsindicate that cream containing 10% of the essential oil from Cymbopogon citratus provided 1071 ± 26.514 seconds ofprotection time against mosquito bites. And the cream containing 15% of the essential oil from Cymbopogoncitratus provided 1097.333 ± 19.139 seconds. It means cream containing 15% of the essential oil is the best formula ofrepellent cream, but does not significantly with cream containing 10 % of the essential oil